Online publishing for improving visibility and access to research publications in Africa (2005)
Online publishing is revolutionizing the way knowledge and information is shared among researchers worldwide. The prospect of online publishing for improving visibility and accessibility of research publications in Africa is examined, issues such a standards and quality control are discussed. Critical infrastructure needed to effectively produce and circulate electronic formats of journals is highlighted. Economic models of online publishing are examined with a view to determine an adoptable model for Africa. The sustainability potential of online publishing for African research especially in library and information science is explicity attended to.